Results of a randomized controlled trial of a decision support intervention for disclosing maternal BRCA genetic test results to children and adolescents - Kenneth P. Tercyak; Tiffani A. DeMarco; Katherine A. Schneider; George Luta; Claudine Isaacs; Judy E. Garber; Marcelo M. Sleiman, Jr.; Mary Rose Yockel; Beth N. Peshkin (PEC Innovation, 2023)
Objective: Evaluate the impact of a targeted family communication intervention for mothers undergoing genetic counseling and testing (GCT) for BRCA gene alterations. Methods: Following BRCA GCT, mothers (N = 204; M age = 45 y) were randomized to either a control condition (self-help print materials) or intervention (printed decision support guide, based on behavioral decision making theory in health care) for supporting choices about disclosing maternal genetic test results to children and adolescents. Behavioral assessments were administered prior to maternal GCT and after receipt of results: primary outcomes were maternal disclosure to children and parent-child communication quality. Results: Mothers in the intervention were > 2x likely to disclose their BRCA test results to their children compared to those in the control condition (odds ratio [OR] = 2.33, 95% confidence interval [CI] = 1.06, 5.10; p = .04). This effect was moderated by children’s ages: mothers of preteens (<13 y) assigned to the intervention were >3x likely to disclose their results (OR = 3.74, 95% CI = 1.49, 9.41; p = .005). In adjusted models, intervention was also associated with favorable changes in the quality of parent-child communication (95% CI = 0.30, 9.00; p < .05). Conclusion: Decision support improves parent-child communication outcomes about GCT for hereditary breast-ovarian cancer. Innovation: This trial is among the first to empirically evaluate the outcomes of a behavioral intervention to support family communication of maternal BRCA risk information to children.